Interplay of confinement and density on the heat transfer characteristics of nanoscale-confined gas. (November 2018) - Rabani, Reza; Heidarinejad, Ghassem; Harting, Jens; Shirani, Ebrahim
Highlights: Effect of wall force field on density and temperature distribution is presented for nanoconfined argon gas. The gas Knudsen number has been changed by variation of the channel height and the gas density. The combined effect of wall force field and channel height on heat transfer characteristics of nanoconfined argon gas is presented. The combined effect of wall force field and gas density on heat transfer characteristics of nanoconfined argon gas is presented. Abstract: The effect of changing the Knudsen number on the thermal properties of static argon gas within nanoscale confinement is investigated by three-dimensional molecular dynamics simulations. Utilizing thermalized channel walls, it is observed that regardless of the channel height and the gas density, the wall force field affects the density and temperature distributions within approximately 1 nm from each channel wall. As the gas density is increased for constant channel height, the relative effect of the wall force field on the motion of argon gas atoms and, consequently, the maximum normalized gas density near the walls is decreased. Therefore, for the same Knudsen number, the temperature jump for this case is higher than what is observed for the case in which the channel height changes at a constant gas density. The normalized effective thermal conductivity of the argon gas based on the heat flux that is obtained by implementation of the Irving–Kirkwood method reveals that the two cases give the same normalized effective thermal conductivity. For the constant density case, the total thermal resistance increases as the Knudsen number decreases while for the constant height case, it reduces considerably. Meanwhile, it is observed that regardless of the method used to change the Knudsen number, a considerable portion of the total thermal resistance refers to interfacial and wall force field thermal resistance even for near micrometer-sized channels. It is shown that while the local thermal conductivity in the near-wall region strongly depends on the gas density, the wall force field leads to a reduced local thermal conductivity as compared to the bulk region.